(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2025)
Question: What is the diversity and taxonomic structure of macrofungi in the Goygol Natıonal Park of Azerbaijan? Locations: Goygol Natıonal Park, Azerbaijan. Methods: field surveys, micromorphology studies follow Prance & Fechner (2017) using a microscope Axio Imager Vert. A1 Carl Zeiss, Germany; identification of species follow Arora (1986), Grunert & Grunert (2002), Horac (2005). Nomenclature: www.indexfungorum.org, www.mycobank.org, www.worldfloraonline.org. Results: The article provides information on the taxonomic composition and ecology of macromycetes, obtained on the basis of fungal samples collected in the territory of the Goygel National Park (Azerbaijan) in 2021–2024. About 130 specimens were newly collected, and 20 specimens kept in the herbarium were used for this study. The purpose of the study was to identify the diversity and taxonomic composition of fungi, as well as to determine the ecological groups of macromycetes in the study area. The work was carried out on the basis of the classical morphological approach (collection, processing of herbarium specimens, identification under a microscope according to the relevant literature). As a result, 80 species were identified belonging to 60 genera, 35 families of such orders as Pezizales, Xylariales, Agaricales, Auriculariales, Boletales, Corticiales, Cantharellales, Geastrales, Hymenochaetales, Polyporales, and Russulales. Among those, Morchella elata represents a new record for Azerbaijan. Based on the analysis of ecological groups, macromycetes were divided into three groups represented by 30 saprotrophs, 25 myco-rrhizal and 5 parasitic species. Some species (Cerioporus squamosus, Fomes fomentarius, Laetiporus sulfureus, and Pleurotus ostreatus) can behave as saprotrophs or parasites. Rare and threatened mushroom species (Agaricus campestris, Coprinus comatus, Laccaria laccata, Lycoperdon perlatum, and Leccinum scabrum) were identified according to the IUCN Red List categories. Studying the macrofungal diversity of Goygol National Park expands our understanding of fungi in the country and provides an opportunity to compare the diversity of the Lesser and Greater Caucasus within Azerbaijan. Recording the diversi-ty of fungi is important along with elucidating their ecological role to suggest their sustainable use in the future. Conclusions: The investigation of the macrofungal diversity of Goygol National Park broadens our understanding of the fungi found in the territory and provides an opportunity to compare the most mushroom-rich regions of the Greater and Lesser Caucasus in Azerbaijan. This will allow us to record and identify the diversity of fungal species and suggest ways to use them effectively in the future.